2007
DOI: 10.1063/1.2437203
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia applicator based on a reentrant cavity for localized head and neck tumors

Abstract: A new applicator based on a reentrant cavity is proposed for treating localized tumors such as those of the head and neck. In order to effectively heat the localized tumor without causing dissipation of heat into the surrounding normal tissues, the electric field must be localized over the target region. Although a small applicator may produce an appropriate localized electric field, the higher resonant frequency due to downsizing of the equipment results in very poor heating distribution; this occurs due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, when the diameter of the reentrant electrode is 100 mm or less, it is expected that the resonant frequency will increase to 200-300 MHz or more. Therefore, we have proposed that dielectrics be inserted into the applicator to avoid the unwanted increase in the resonant frequency due to miniaturization [18]. In this paper, a numerical analysis reveals that the resonant frequency can be reduced by increasing the volume of the dielectrics inserted into the applicator.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, when the diameter of the reentrant electrode is 100 mm or less, it is expected that the resonant frequency will increase to 200-300 MHz or more. Therefore, we have proposed that dielectrics be inserted into the applicator to avoid the unwanted increase in the resonant frequency due to miniaturization [18]. In this paper, a numerical analysis reveals that the resonant frequency can be reduced by increasing the volume of the dielectrics inserted into the applicator.…”
Section: Introductionmentioning
confidence: 97%
“…The electric parameters used in this analysis are shown in table 1. The resonant frequency of the resonator was calculated under conditions in which the stored energies expressed in terms of the electric field energy and magnetic field energy were maximum[18].…”
mentioning
confidence: 99%
“…Since an intense electric field is produced in the gap between the reentrant electrodes, a standing wave electric field distribution is formed in the living body when it is placed in the gap; thus, a deep region in the body can be heated effectively. Based on this concept, we have developed a general applicator, which is shown in Figure 1, and have demonstrated its feasibility by numerical and animal experiments [11][12][13][14]. However, since the region where the electric field is concentrated is relatively large, it is difficult to achieve further localization to safely heat the early small tumors, for example, tumors of the head and neck.…”
Section: Introductionmentioning
confidence: 99%
“…Through numerical and experimental analyses, we indicated that localized heating with this method is possible [3], [4]. In addition, we attempted to reduce the size of the applicator [5], [6] as well as optimizing the applicator using experimental design methods [7] in order to improve the therapeutic effect of a cancer, and showed that the electric field distribution between the reentrant electrodes can be localized within a space region of 70-80 mm in diameter. However, when the subject of treatment is a small cancer localized in the head and neck lesion, a region of 30-50 mm in diameter must be selectively heated and thus the heating characteristics achieved in previous studies are still insufficient.…”
Section: Introductionmentioning
confidence: 99%